Prediction of whelping date in large and giant canine breeds by ultrasonography foetal biometry. (3rd August 2016) - Alonge, S.; Beccaglia, M.; Melandri, M.; Luvoni, G. C.
Abstract : OBJECTIVES: To derive the growth curves of the inner chorionic cavity and the biparietal diameter in large and giant dog breeds by ultrasonographic foetal biometry. To evaluate their accuracy in the prediction of whelping date and the effect of litter size and foetal sex ratio. METHODS: Foetal biometry parameters were obtained using serial ultrasonographic examinations in eight large (26 to 40 kg) and nine giant (>40 kg) pregnant bitches with known breeding dates and concentrations of serum progesterone during oestrus. The relationship between inner chorionic cavity or biparietal diameter growth and days to parturition were analysed by linear regression and the equations derived from the growth curves were applied to predict the whelping day. The accuracy of the prediction (whelping day ±1 day and ±2 days) and the litter size and sex ratio were recorded. RESULTS: The results showed a significant relationship between days before parturition and inner chorionic cavity or biparietal diameter. The overall accuracy at ±2 days was greater, than that at ±1 day. In giant breed bitches, the accuracy of the prediction by biparietal diameter was significantly lower in small, than normal litter size. No effect of foetal sex ratio was observed. CLINICAL SIGNIFICANCE: Foetal biometry parameters obtained by ultrasonography can be used to predict whelping dates in large and giant dog breeds.